Prevalence of Refractive Errors among Primary School Children in the Southern Region of Bangladesh - Ul Kadir, Syeed Mehbub; Ali, Mahar; Islam, Md Shirajul; Parvin, Rukhsana; Quadir, ASM; Raihani, Mostafa Jahir; Islam, AKM Rafiqul; Ahmmed, Saifuddin (Community Based Medical Journal, 2022)
Refractive errors are considered as avoidable conditions which may lead to visual disabilities in children. A cross-sectional study was conducted between January and May of 2021 in a tertiary level specialized eye hospital in the southern region of Bangladesh to assess the refractive errors among primary (elementary) school children. Our study population was all the primary school children attending the outpatient department of the hospital. However, we used convenient sampling in the study. A total of 252 primary school-going children were examined – 148(58.7%) boys and 104(41.3%) girls. Among them, the minimum age was seven years, and the maximum age was 12 years. The mean age of the children was 9.67 years. Among the refractive errors, myopia was the highest prevalent condition (103 children, 50%), followed by astigmatism (77 children, 37.4%), and hyperopia (26 children, 12.6%). Among astigmatism, myopic astigmatism was 58(75.3%), while mixed astigmatism was observed in 13(17%) children and hyperopic astigmatism was found in 6(7.8%) children. The amblyopia was noted in 17 children (6.7%). The visual acuity was improved after corrections of the refractive errors. CBMJ 2022 January: vol. 11 no. 01 P: 41-45